Survival benefit of adjuvant chemotherapy following neoadjuvant therapy and oesophagectomy in oesophageal adenocarcinoma. Issue 9 (September 2022) - Kamarajah, Sivesh K.; Markar, Sheraz R.; Phillips, Alexander W.; Kunene, Victoria; Fackrell, David; Salti, George I.; Dahdaleh, Fadi S.; Griffiths, Ewen A.
Abstract: Background: The evidence assessing the additional benefits of adjuvant chemotherapy (AC) following neoadjuvant therapy (NAT; i.e. chemotherapy or chemoradiotherapy) and oesophagectomy for oesophageal adenocarcinoma (EAC) are limited. This study aimed to determine whether AC improves long-term survival in patients receiving NAT and oesophagectomy. Methods: Patients receiving oesophagectomy for EAC following NAT from 2004 to 2016 were identified from the National Cancer Data Base (NCDB). To account for immortality bias, patients with survival ≤3 months were excluded to account for immortality bias. Propensity score matching (PSM) and Cox regression was performed to account for selection bias and analyze impact of AC on overall survival. Results: Overall, 12, 972 (91%) did not receive AC and 1, 255 (9%) received AC. After PSM there were 2, 485 who did not receive AC and 1, 254 who did. After matching, AC was associated with improved survival (median: 38.5 vs 32.3 months, p < 0.001), which remained after multivariable adjustment (HR: 0.78, CI95% : 0.71–0.87). On multivariable interaction analyses, this benefit persisted in subgroup analysis for nodal status: N0 (HR: 0.85, CI95% : 0.69–0.96), N1 (HR: 0.66, CI95% : 0.56–0.78), N2/3 (HR: 0.80, CI95% : 0.66–0.97) and margin status: R0 (HR: 0.77, CI95% : 0.69–0.86), R1 (HR: 0.60, CI95% : 0.43–0.85). Further, patients with stable disease following NAT (HR: 0.60, CI95% : 0.59–0.80) or downstaged (HR: 0.80, CI95% : 0.68–0.95) disease had significant survival benefit after AC, but not patients with upstaged disease. Conclusion: AC following NAT and oesophagectomy is associated with improved survival, even in node-negative and margin-negative disease. NAT response may be crucial in identifying patients who will benefit maximally from AC, and thus future research should be focused on identifying molecular phenotype of tumours that respond to chemotherapy to improve outcomes.